PERUBAHAN TINGKAH LAKU SISWA MELALUI KOMUNIKASI ANTAR PRIBADI GURU PENDIDIKAN AGAMA ISLAM - Latifah Latifah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
This study describes systematically changes in student behavior through interpersonal communication of Islamic Education teachers at Madrasah Ibtidaiyah Assalam Martapura. Focusing on changing behavior and helping teachers to implement good behavior to their students. This behavior change includes: a) Interactive involvement, this behavior change determines the level of one's participation and participation in communication with other people, including: responsiveness, perceptive attitude and attentiveness. b). Interaction management, this change in behavior helps a person be able to take useful actions for someone to achieve communication goals. c) Behavioral flexibility, this change in behavior helps a person to carry out various possible behaviors that can be taken to achieve communication goals. d) Listening, this behavior change helps someone to be able to listen to people who communicate with someone not only content, but also the feelings, concerns, and worries that accompany it. e) Social style, this behavior change helps someone to behave attractively, distinctively, and can be accepted by those who communicate with that person. f) Communication anxiety, this behavior change can overcome fear, confusion, and confusion of thought, body shaking, and stage fright that appears in communicating.